XI Conference of the International Society for Quality-of-Life Studies (ISQOLS) "Discovering New Frontiers in Quality of Life Research" (1-4 November 2012, Venice, Italy). Issue 1 (July 2013) - Maggino, Filomena
This report on the recent eleventh conference of the International Society for Quality of Life Studies (ISQOLS), which took place in Venice, traces the development of methods and movements involved in measuring quality of life, including the new BES project, established at the Italian National Institute of Statistics, and the initiative "How is Life", led by OECD.